Prescribing and Rationality of Diabetes Therapy - Adrian Mulya; Denia Pratiwi; Isna Wardaniati; Junisa Prahestina (Poltekkes Kemenkes Riau, 2026)
Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose due to impaired insulin secretion or action. This study aimed to analyze prescribing patterns and evaluate the rationality of antidiabetic therapy in hospitalized patients with type 2 diabetes mellitus at Arifin Achmad Regional General Hospital, Pekanbaru, during 2021–2023. A retrospective cross-sectional study was conducted using 76 eligible medical records. Most patients were female (57%) and aged 45–54 years. Insulin monotherapy, particularly novorapid, was the most commonly prescribed treatment, followed by metformin and combination insulin therapy. Rationality assessment showed that most prescriptions met criteria for appropriate indication, drug selection, dosage, patient suitability, and dosing interval. However, potential drug interactions were identified, mainly of moderate severity. In conclusion, prescribing patterns were generally rational, although monitoring of potential drug interactions remains necessary to ensure safe and effective therapy.